Maintaining integrity in the face of death: the views and experiences of people affected by lung cancer in discussing preferences and wishes for end of life care - Horne, Gillian Doris (2011)
This thesis explores the views and experiences of people with lung cancer, and family members, of discussing preferences and wishes for end of life treatment and care. It presents an interpretive analysis based on the application of a constructivist grounded theory approach. Study participants included: eighteen men and seven women with lung cancer and nineteen family members. Participants were mainly from lower socio-economic groups living in the north of England. Single, joint and group interviews were used to gather data. Interview transcripts were analysed using a constant comparative method and conceptual models were drawn to aid the development of the theoretical interpretation.